THE IMPACT OF EXERCISES USING THE VISUAL LEARNING STRATEGY ON LEARNING SOME BASIC GYMNASTICS SKILLS FOR FEMALE STUDENTS - Rahman Mazhar, Noor; Mohammed Amin, Hind; Ghazi Hassan, Ala Salam (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The process of equipping learners with modern teaching strategies is one of the primary concerns of those responsible for the education system. This requires awareness of teachers' knowledge of these strategies to ensure proper planning and execution in the classroom. The significance of this study lies in the following points:The research aims to design exercises based on the visual learning strategy for teaching some basic gymnastics skills to female students.The researcher hypothesizes a positive impact of the visual learning strategy on learning some basic gymnastics skills among female students.The researcher utilized an experimental approach with pre- and post-tests in accordance with the nature of the study's problem.The research population included 26 female second-year students from the College of Physical Education and Sports Sciences at the University of Kufa. A random sample of 20 students was selected to represent the research sample. The researcher concluded that the visual learning strategy has a significant positive impact on learning some basic gymnastics skills for female students